Prognostic factors in acinic cell carcinoma of the head and neck: The Amsterdam experience. (February 2022) - van Weert, Stijn; Valstar, Matthijs; Lissenberg-Witte, Birgit; Bloemena, Elisabeth; Smit, Laura; van der Wal, Jacqueline; Vergeer, Marije; Smeele, Ludi; Leemans, C.René
Highlights: Conventional acinic cell carcinoma has a good long term outcome in a large two- center study with comparable treatment strategies. The incidence of nodal disease and perineural invasion is low. Patients with acinic cell carcinoma need long term follow up due to frequent late development of recurrence. High grade transformation (HGT) in acinic cell carcinoma is not rare (21% incidence in the current study) and should be considered a specific entity within the spectrum of acinic cell carcinoma with a tendency for short term recurrence both loco- regional and distant. The threshold for elective neck dissection in acinic cell carcinoma patients should be low considering the relative high incidence of HGT and the relative low accuracy of cytology in correctly identifying HGT preoperatively. Abstract: Introduction: The aim was to analyse prognosticators in acinic cell carcinoma (AciCC) in two head and neck referral centers in Amsterdam, the Netherlands. Materials and methods: Eighty- nine cases of AciCC treated between 1979 and 2016 were retrospectively reviewed. Five, − 10 -and 20- year estimates of survival were executed as well as univariate analysis of prognosticators. Results: The majority of AciCC were T1-T2; 89%. Two percent had nodal disease (2%). The most affected organ was the parotid gland (84%) with a female preponderance (67%). Mean age was 52 years with most cases diagnosed in the fourth to sixth decade. The majority of patients received adjuvant radiotherapy. Elective neck dissection (END) in the N0 neck showed no metastases. High grade transformation (HGT) was found in 21% of cases. Median follow up was 101.9 months. Median time to recurrence was 26 months. Nine patients developed distant metastases (DM) of whom 6 had HGT-AciCC. Median survival with DM was 7 months. Five, - ten -and twenty- year estimates were 84%, 81% and 81% for recurrence free survival respectively. Negative clinical features were advanced stage disease and tumour size > 2.6 cm. Negative histological features were a high mitotic rate, HGT, close and involved surgical margins and necrosis. Conclusion: AciCC- HGT excluded- of the head and neck has an excellent prognosis and shows acceptable long term results. END can be considered as part of the standard treatment due to the relative high incidence of HGT- AciCC and low accuracy of cytology.